Internal carotid artery plication following carotid endarterectomy: our experience: Plikacija notranje karotidne arterije: naše izkušnje - Flis, Vojko; Tetičkovič, Erih; Mrdža, Božidar; Miltoić, Franko; Štirn, Barbara; Kobilica, Nina; Bergauer, Andrej (Acta Medico-Biotechnica, 2021)
Purpose: Apart from obliterative processes, carotid insufficiency may be caused by stenosis due to abnormal elongation and kinking of the vessel. Among shortening procedures to correct elongation, we prefer the plication technique. The aim of this study was to present our experience with internal carotid artery (ICA) plication following carotid endarterectomy (CEA). Methods: A retrospective study was conducted on 323 patients (mean age 67 years) with 376 CEA performed between January 2000 and January 2006. Indications for operation included ipsilateral stroke in 34 (9 %), TIA in 81 (21.5 %), amaurosis fugax in 15 (4 %) and asymptomatic stenosis or nonhemispheric symptoms in 246 (65.5 %). All patients had preoperative and postoperative duplex scan. All patients had extended clinical and biochemical assessment and a preoperative duplex, CT and TCD scan. Conventional surgical technique was used with general anesthesia, perioperative and postoperative transcranial Doppler monitoring, regular shunting and routine patching. In 32 (8.5 %) CEAs, we found it necessary to shorten a segment of the ICA by plication. Early postoperative results were assessed on the basis of clinically significant postoperative embolization (defined as >25 emboli in any 10 minute period) and or any stroke or death. Secondary endpoints included residual and recurrent stenosis (>50%) on operated artery, operative site hematomas, cranial nerve injury and other complications, related to surgery. Results: Among 32 plicated patients there were no intra or postoperative neurological events. Postoperatively the incidence of residual stenosis on the one week scan was 3.1 % (1 CEA) and that of recurrent (> 50 %) restenosis 6.2 % (2 CEAs). There was no mortality in the plicated group. Among 344 non-plicated CEAs there were two perioperative deaths (0.6 %) and seven postoperative strokes (2 %). One patient in plication group (3.1%) and 18 patients in simple CEA group (5%) received Dextran postoperatively on the basis of significant postoperative embolization (hi square=0,27, p>0.5). Differences were not statistically significant. The incidence of residual stenosis was 3.5 % (7 CEAs) and of recurrent stenosis 4.9 % (17 CEAs)–hi square 0.1, p>0.5. Differences were not statistically significant. Conclusion: ICA plication during CEA can be performed safely. In our study the presented technique was not associated with an increased incidence of perioperative and early postoperative complications.